Baroreflex Impairment After Subarachnoid Hemorrhage Is Associated With Unfavorable Outcome. Issue 7 (July 2018) - Nasr, Nathalie; Gaio, Rita; Czosnyka, Marek; Budohoski, Karol; Liu, Xiuyun; Donnelly, Joseph; Sykora, Marek; Kirkpatrick, Peter; Pavy-Le Traon, Anne; Haubrich, Christina; Larrue, Vincent; Smielewski, Peter
Abstract : Background and Purpose—: Aneurysmal subarachnoid hemorrhage (SAH) is characterized by important changes in the autonomic nervous system with potentially adverse consequences. The baroreflex has a key role in regulating the autonomic nervous system. Its role in SAH outcome is not known. The purpose of this study was to evaluate the association between the baroreflex and the functional 3-month outcome in SAH. Methods—: The study used a prospective database of 101 patients hospitalized for SAH. We excluded patients receiving β-blockers or noradrenaline. Baroreflex sensitivity (BRS) was measured using the cross-correlation method. A good outcome was defined by a Glasgow Outcome Scale score at 4 or 5 at 3 months. Results—: Forty-eight patients were included. Median age was 58 years old (36–76 years); women/men: 34/14. The World Federation of Neurosurgery clinical severity score on admission was 1 or 2 for 73% of patients. In the univariate analysis, BRS ( P =0.007), sedation ( P =0.001), World Federation of Neurosurgery score ( P =0.001), Glasgow score ( P =0.002), Fisher score ( P =0.022), and heart rate ( P =0.037) were associated with outcome. The area under the receiver operating characteristic curve for the model with BRS as a single predictor was estimated at 0.835. For each unit increase in BRS, the odds for a good outcome were predicted to increase by 31%. Area under the receiver operating characteristic curve for heart rate alone was 0.670. In the multivariate analysis, BRS (odds ratio, 1.312; 95% confidence interval, 1.048–1.818; P =0.018) and World Federation of Neurosurgery (odds ratio, 0.382; 95% confidence interval, 0.171–0.706; P =0.001) were significantly associated with outcome. Area under the receiver operating characteristic curve was estimated at 0.900. Conclusions—: In SAH, early BRS was associated with 3-month outcome. This conclusion requires confirmation on a larger number of patients in a multicentre study.